Culturally Rooted MSME Strategies: Integrating Local Wisdom into Cultural Tourism Development in Sulawesi - Dipoatmodjo, Tenri Sayu Puspitaningsih (Abadi Institute, 2025)
This study investigates how local wisdom can be systematically integrated into the strategic development of cultural tourism MSMEs across Sulawesi’s diverse ethnic landscapes. Drawing on a qualitative multi-site case study approach, the research examines how cultural values—such as sipakatau, ma’bulo sibatang, and siri’ na pacce—shape entrepreneurial practices, organizational resilience, and community-oriented business models. Data collected through interviews, participant observation, focus groups, and document analysis reveal three primary integration pathways: symbolic reinforcement in branding and storytelling, operational cooperativeization rooted in kinship-based production systems, and strategic alliances with cultural councils and NGOs that institutionalize cultural integrity. The findings highlight both the strategic benefits and persistent barriers—including digital capability gaps, rigid funding schemes, and bureaucratic certification processes. The study argues that meaningful integration of local wisdom requires community-led governance, culturally sensitive institutional support, and participatory mechanisms that prevent cultural commodification from becoming extractive. By reframing entrepreneurship as a relational and ethical activity, the research offers actionable strategies such as culturally grounded digital incubators, micro-grant schemes tied to stewardship criteria, and regional MSME cooperation networks. Overall, the study positions cultural authenticity not as a constraint but as a competitive and ethical foundation for sustainable cultural tourism in Sulawesi.